Rendement and Characteristics of Wood Vinegar Produced from Ironwood Delinquent Waste through Clay Kiln Charcoaling Furnace - Muhammad Faisal Mahdie; Violet Violet; Muhammad Helmi (Journal of Wetlands Environmental Management, 2020)
The study aimed to determine the rendement of charcoal and wood vinegar and to identify wood vinegar chemical compounds made from ironwood deliquent waste. The study was carried out by using charcoaling facilities at the charcoaling center in the village of Asam – Asam. The charcoal and wood vinegar rendements were determined after ironwood delinquent waste was heated for 21 days with a temperature of approximately 400 - 600 ºC. The results showed that the rendement of the charcoal and wood vinegar were 14.02% and 0.05%, respectively. The research with wood vinegar characteristic before purification was pungent, however after purification, the results did not sting; color pH before purification was blackish-brown, however after purification it was pale brown yellow; the specific gravity before purification was 1.012 and after purification, it was 0.97; the pH before purification is 3.63 and after purification 3.41; and acid content before purification was 3.73% and after purification it was 3.66%. As a whole, the physics test of wood vinegar is categorized in Japan standard, however, the color only before purification is not standard. There are five chemical compounds identified in wood vinegar both before and after purification.